Dripper Irrigation Monitoring System for Chili Fertigation Using EC-GSM - Mohamad Fuad, Mohamad Nursholehan; Mohamad, Nor Zulaily (Evolution in Electrical and Electronic Engineering, 2021)
Fertigation is the process of supplying plant nutrients along with water to produce a quality crop with higher yields. The use of an automated fertigation system can help farmers significantly improve their water and nutrient use. In the fertigation system, the efficiency of irrigation will decrease because of the clogged dripper. Therefore, in order to achieve high irrigation efficiency, the clogged dripper should be repaired as soon as possible to prevent the growth of chilies stunted by malnutrition. In this paper, the efficiency of the fertigation system was analyzed. The objective of the study is to automatically monitor the dripper that has been clogged by impurities due to fertilizer, dry soil, and so on and to develop a communication system to help the farmers. The communication system uses a GSM module to send data information to the user. Arduino is selected as the microcontroller to program the system. The soil moisture sensor is used for this project in order to detect the clogged dripper. With the proposed system, this project is looking forward to the best method for improving the efficiency of fertilization. Apart from that, the concept of a water flow feedback mechanism is executed in order to improve the accuracy of the proposed system. The system has been built accordingly and the performance of the system is tested. As a consequence, the result shows that the system is able to run and the overall concept of the system can be implemented for the real application of the fertigation system. Last but not least, this project looks forward to providing high-quality fertilization practices to farmers, and at the same time expanding monitoring systems in fertilization technology to the international market.